2011
DOI: 10.1016/j.maturitas.2011.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Progestogens and venous thromboembolism among postmenopausal women using hormone therapy

Abstract: Hormone therapy (HT) is the most effective treatment for correcting menopausal symptoms after menopause. HT initially consisted of estrogens alone and progestogens were secondly added to estrogens for preventing the risk of endometrial cancer associated to estrogens use. Venous thromboembolism (VTE), including deep vein thrombosis and pulmonary embolism, is a major harmful effect of HT. It is now well known that oral and transdermal estrogens are differentially associated with VTE risk but progestogens may be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 69 publications
0
27
0
2
Order By: Relevance
“…A recent international clinical guideline recommended that progesterone be used in women with increased risk for thromboembolism 6 because it is without any signal of increased clot risk 47,71 .…”
Section: Venous and Arterial Adverse Clottingmentioning
confidence: 99%
“…A recent international clinical guideline recommended that progesterone be used in women with increased risk for thromboembolism 6 because it is without any signal of increased clot risk 47,71 .…”
Section: Venous and Arterial Adverse Clottingmentioning
confidence: 99%
“…In the Women's International Study of long Duration Estrogen after Menopause (WISDOM) trial, the results showed that users of CEE plus MPA had a higher thrombotic risk than those who used CEE alone; however, the difference in VTE risk did not reach statistical significance (HR = 2.39; 95%/CI: 0.62-9.24) [52]. In a study by Canonico et al [53], there was uncertainty regarding the impact of pregnane and 19-nortestosterone derivatives on VTE risk (OR = 1.3; 95% CI: 0.9-2.0 and OR = 1.4; 95% CI = 0.7-2.4, respectively), partly due to lack of statistical power for subgroup analysis.…”
Section: Effects On Clottingmentioning
confidence: 99%
“…[25] The route of delivery will impact on risk, with the highest risk being associated with oral EPT, followed by oral ET, and the lowest risk being associated with transdermal HT. [26,27] …”
Section: Ht and Venous Thromboembolism (Vte)mentioning
confidence: 99%